A comparison for different wall-boundary conditions for kinetic theory based two-fluid models. (May 2015) - Soleimani, Afsaneh; Schneiderbauer, Simon; Pirker, Stefan
Highlights: We compared wall boundary conditions (BC) for kinetic theory based two-fluid models. Li and Benyahia BCs overestimate the granular temperature in the all sliding regime. Jenkin's model reveals poor predictions of transition between sliding and no-sliding. Johnson and Jackson's theory appears inappropriate in the all sliding regime. The most complete theory appears to be the BCs ofSchneiderbauer et al. (2012a) .